Flavonoid-Conjugated Gadolinium Complexes as Anti-Inflammatory Theranostic Agents - Byeong Woo Yang; Sohyeon Yang; Soyeon Kim; Ah Rum Baek; Bokyung Sung; Yeoun-Hee Kim; Jung Tae Lee; Sang Yun Lee; Hee-Kyung Kim; Garam Choi; Ji-Ae Park; Sung-Wook Nam; et al. (MDPI AG, 2022)
In this study, we designed, synthesized, and evaluated gadolinium compounds conjugated with flavonoids as potential theranostic agents for the treatment of inflammation. These novel theranostic agents combine a molecular imaging agent and one of three flavonoids (galangin, chrysin, and 7-hydroxyflavone) as anti-inflammatory drugs as a single integrated platform. Using these agents, MR imaging showed contrast enhancement (>10 in CNR) at inflamed sites in an animal inflammation model, and subsequent MR imaging used to monitor the therapeutic efficacy of these integrated agents revealed changes in inflamed regions. The anti-inflammatory effects of these agents were demonstrated both in vitro and in vivo. Furthermore, the antioxidant efficacy of the agents was evaluated by measuring their reactive oxygen species scavenging properties. For example, Gd-galangin at 30 μM showed a three-fold higher ROS scavenging of DPPH. Taken together, our findings provide convincing evidence to indicate that flavonoid-conjugated gadolinium compounds can be used as potentially efficient theranostic agents for the treatment of inflammation.